Política de segurança pública : ciência e gestão na prevenção à criminalidade em Uberlândia-MG - Bonesso, Márcio (2015)
As the main objective of the research, sense connections between social theories and methods of management of public security policies were created, having as study of locus the state policies of crime prevention in the city of Uberlândia in Minas Gerais. The implementation of these new policies in the provincial town had a different reality from where they were planned, the capital city of Belo Horizonte. In this context, as the specific objective of the research, the relationship between the history of city social control with the impact of these state security policies were studied. As an analytical deployment, this research has a theoretical review questioning bonds of social theories and international, national and state interventional programs in the dynamic city of Uberlandia. Regarding the articulation between the axes of qualified repression and social protection, the municipal field of study propiciated the descripition of the macro-implementation of public security policies and micro-social experiences of prevention policies against crime in the suburbs classified as risk areas. Through a comparative analysis the research used different methodological resources to get the desired results: crime statistics, documents of the CPI Drug Trafficking, regulatory manuals on public safety programs and crime prevention, minutes of network meetings, theses, dissertations and scientific articles, land registry cerificates; ethnographic observations on: the utilities and anti utilities markets in the use and trafficking of illegal drugs on the promotion of community networks, art networks, sports networks and workshops of crime prevention programs; and finally, interviews were conducted with residents and supra-local professionals from various locations. The results showed that in Uberlândia there were in some poor neighborhoods a primacy of the axis of qualified repression on the axis of social protection, with the expansion of specialized policing without including compatible employees connected to prevention programs. However, it is noteworthy that the social actions of these officials, although certain structural problems in many micro-social contexts also favored the extension of public services for the population of poor localities. Thus, Uberlandia has become a multifaceted research locus with experiences that moved between conservative and innovative actions, triggered by various individuals and social institutions with multiple motivations.